2010
DOI: 10.1186/1471-2458-10-105
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity and effectiveness of a Nevirapine-based antiretroviral therapy in HIV-infected patients with or without viral hepatitis B or C infection in Cameroon

Abstract: BackgroundCoinfection with hepatitis B virus (HBV) or hepatitis C virus (HCV) in HIV-infected patients receiving a commonly used nevirapine-based antiretroviral therapy is a major concern for African clinicians owing to its high prevalence, the infrequent testing and treatment of viral hepatitis, and the impact of liver disease on the tolerability and effectiveness of anti-HIV treatment. We compared the hepatotoxicity and the immunological, virological and clinical effectiveness of a nevirapine-based antiretro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 30 publications
1
23
1
Order By: Relevance
“…Lower results were also found in a study conducted in Tanzania which found 0.3% severe hepatotoxicity [1] while a higher prevalence of 7% was found in a study done in Cameroon in mono-infected patients [18]. This difference from the Cameroon study could be due to different treatment regimens and different study designs.…”
Section: Discussionmentioning
confidence: 79%
“…Lower results were also found in a study conducted in Tanzania which found 0.3% severe hepatotoxicity [1] while a higher prevalence of 7% was found in a study done in Cameroon in mono-infected patients [18]. This difference from the Cameroon study could be due to different treatment regimens and different study designs.…”
Section: Discussionmentioning
confidence: 79%
“…Of the 48 independent cohorts, 31 reported results from the overall cohort [24, 62, 6492], while 17 reported results from two different groups within the cohort [59, 93108], although for two of these studies, only one group was considered in our meta-analysis due to sample size restriction [100, 107]. This gave 63 distinct populations.…”
Section: Resultsmentioning
confidence: 99%
“…6 However, nevirapine hepatotoxicity occurs at higher HIV CD4+ counts than those at which patients in sub-Saharan Africa begin ART, and safe use of nevirapine-based regimens has been suggested in patients where CD4 count is low irrespective of HBV and HCV co-infections. 7 …”
Section: Introductionmentioning
confidence: 99%